2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611161
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a chondrocyte cell sheet using temperature-responsive poly(N-isopropylacrylamide)-co-acrylamide

Abstract: In this study, a novel temperature-responsive poly(N-isopropylacrylamide)-co-acrylamide was used to prepare a chondrocyte cell sheet. Chondrocytes were isolated from human articular cartilage and plated on the copolymer film grafted tissue culture plates. The cell attachment on the copolymer film was shown to be similar to that of the ungrafted surface. To harvest a cell sheet, the incubation temperature was reduced to 10°C for 30 minutes to allow the polymer chain to fully extend, changing the copolymer's pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Adhesion forces between the cell and the surface are lost upon polymer hydration. However, the cell and extracellular matrix (ECM) protein interactions are still active 4,11,15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesion forces between the cell and the surface are lost upon polymer hydration. However, the cell and extracellular matrix (ECM) protein interactions are still active 4,11,15 …”
Section: Introductionmentioning
confidence: 99%
“…6 In an aqueous environment, PNIAM shows a hydrophilic-hydrophobic phase transition at its lower critical solution temperature (LCST) of about 32 C. [7][8][9][10] When the temperature is above the LCST, cells adhere to the PNIAM surface as the polymer chains collapse, allowing proteins to adsorb to the surface. [11][12][13] In contrast, the adsorption of protein and cell attachment is negligible below the LCST due to extended chain conformation. As a result, cultured cells along with their adhesion proteins can be recovered as a monolayer cell sheet when the temperature is below the LCST.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have focused on attempts to fabricate a temperature-sensitive surface, which can be used for detachment of different cell types. ,, The use of ultraviolet (UV) is a more economical alternative, compared to EB irradiation. , In addition, it can be used in conjunction with other techniques, such as surface patterning and photolithography techniques, to graft polymers onto TCPS. , Our previous studies showed that temperature-sensitive Poly­( N -isopropylacrylamide- co -acrylamide) (PNIAM- co -AM) can be grafted onto TCPS by UV irradiation. , When harvesting cell sheets, the cell monolayers had to be agitated with the culture media. This, however, resulted in 85% detachment of mouse preosteoblast MC3T3-E1 cell sheets.…”
Section: Introductionmentioning
confidence: 99%